2021
DOI: 10.23887/jet.v5i1.31435
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of The Use of Multimedia Flip Book With the Flipped Classroom Approach in Vocational School

Abstract: The problem encountered in learning operating system teaching materials majoring in network computer engineering is the lack of creativity in students' thinking skills so that they experience obstacles in the practical process. This study used a quasi-experimental design with a pretest-posttest Control Group Design. Data collection techniques using tests. The pre-test was carried out at the beginning to see the students' initial abilities before being given treatment, the post-test was carried out to test the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…The flipped classroom is learning that makes students learn independently. Students learn first about the topics before meeting with the teacher, and, for the problem-solving exercise process, it is used as homework (Dombrowski et al, 2018;Oktarina et al, 2021). Learning that familiarizes students to solve problems affects the development of critical thinking skills.…”
Section: Skills Approach_learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The flipped classroom is learning that makes students learn independently. Students learn first about the topics before meeting with the teacher, and, for the problem-solving exercise process, it is used as homework (Dombrowski et al, 2018;Oktarina et al, 2021). Learning that familiarizes students to solve problems affects the development of critical thinking skills.…”
Section: Skills Approach_learningmentioning
confidence: 99%
“…The flipped classroom is learning that makes students learn independently because they have studied at home first about the topics to be studied before meeting with the teacher and for problem-solving exercises (Dombrowski et al, 2018;Oktarina et al, 2021). Flipped classroom creates a learning environment that is technology-driven and student-centered at the same time (Leanna & Petra, 2021;Wikanda et al, 2021), thereby encouraging learning and practice according to individual pace and schedule (Cheng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is textbooks (Basyah, 2018), electronic modules (Wirasatriya et al, 2020), interactive electronic books (containing text, audio, and video) (Oktarina et al, 2021), and Youtube (Pudjianto et al, 2021), which found effective for delivering materials. It is group discussion sheets (Usmadi and Ergusni, 2019), student worksheets (Wirasatriya et al, 2020), and practicum guidebooks (Basyah, 2018) that are used as learning tools.…”
Section: The Implementation Of Flipped Classroommentioning
confidence: 99%
“…However, determining which media to use cannot be separated from considering the characteristics of students in learning and students' readiness to use learning media or tools. Oktarina et al (2021) claimed that using material videos or other forms of material is not the most determining factor for learning success. Without a suitable instructional design, learning would not be optimal.…”
Section: The Implementation Of Flipped Classroommentioning
confidence: 99%
“…Proses pembuatan flipbook digital mudah di desain dengan menggunakan aplikasi corel draw kemudian dimasukkan dalam web flippingbook, Penggunaan media flipbook digital dipadukan dengan model pembelajaran flipped mastery classroom diharapkan mampu membuat pembelajaran lebih efektif dan tentunya akan berimbas terhadap hasil belajar siswa secara positif. Model dan media ini membuat siswa semakin aktif selama kegiatan pembelajaran di dalam kelas sebab siswa sudah mempelajari materi pembelajaran melalui media flipbook Hasil penelitian ini selaras dengan penelitian Albar et al, (2021); Oktarina et al, (2021); Said & Zainal (2017), tentang pengaruh model pembelajaran flipped mastery classroom dan penggunaan media flipbook digital berpengaruh positif terhadap hasil belajar siswa. Pencapaian keberhasilan peningkatan hasil belajar dengan flipped mastery classroom yang dilakukan disebaban karena model tersebut menyediakan waktu yang lebih leluasa bagi siswa dalam mempelajari materi pembelajaran serta ketersedian media flipbook digital memudahkan siswa karena dapat diputar berulang-ulang jika siswa lupa dengan materi yang telah dilalui.…”
Section: Pembahasan Pengaruh Model Pembelajaran Flipped Mastery Class...unclassified